Companson of personality beliefs between depressed patients and healthy controls - Turkcapar, Mehmet Hakan; Yucens, Bengu; Kuru, Erkan; Safak, Yasir; Karadere, Mehmet Emrah (W B SAUNDERS CO-ELSEVIER INC, 2014)
Introduction: According to the cognitive model, the common mechanism underlying all psychological disorders is distorted or dysfunctional thoughts that affect mood and behaviors. Dysfunctional thoughts predispose an individual to depression and are among the processes that form the basis of personality traits. Elucidating the personality beliefs associated with depression and dysfunctional thoughts is important to understanding and treating depression. The aim of the present study is to determine whether depressed patients exhibited pathological personality beliefs compared with healthy controls. Furthermore, we investigated which personality beliefs were more common among such depressed patients. Methods: A total of 70 patients who were admitted to the Department of Psychiatry at Ankara Diskapi Yildirim Beyazit Training and Research Hospital (Ankara, Turkey) and diagnosed with major depressive disorder according to The Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) diagnostic criteria were included in the study. Additionally, 70 healthy controls matched for age, marital status, and education were included in the study. The Sociodemographic Data Form and Personality Belief Questionnaire-Short form (PBQ-SF) were administered to the participants. Results: A comparison of the depression group with the healthy controls revealed higher scores in dependent, passive aggressive, obsessive compulsive, antisocial, histrionic, paranoid, borderline, and avoidant personality subscales in the depressive group. Conclusions: These results suggest that personality beliefs at the pathological level are more common in depressive patients and that the detection of these beliefs would be useful for predicting the prognosis of the disease and determining appropriate treatment methods. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: NATIONAL EPIDEMIOLOGIC SURVEY; MAJOR DEPRESSION; DISORDERS; ALCOHOL; QUESTIONNAIRE; COOCCURRENCE; COMORBIDITY; UNIPOLAR; THERAPY; BIPOLAR